A Review of Anatomical and Histological Features of the Thyroid Gland In Different Species of Animals - Mahmood, Hussein, B.; Obead, Walaa, F.; Dawood, Ghassan A. (Diyala Journal for Veterinary Sciences, 2023)
This study includes main morphological features such as, the shape of glands, location and dimensions. These features to provide data for the medical and surgical science. In the anatomical structures that appear similar in laboratory animals, but are different in some histological features, in domestic animals, the thyroid gland is encased in a thin or thick capsule of dense, irregular connective tissue. The follicular cells have different shapes depending on the gland's functional ability both during maturation and in response to external influences. In addition. The thyroid gland demonstrated a seasonal change in the amount of colloidal matter and the height of the follicular cells. The follicles are huge and the follicular cells are flattened while the gland is dormant, but they are tiny when it is active due to the abundance of colloid. In the thyroid gland of different species, the parafollicular cells are not generally distributed diffusely throughout the gland but tend to be concentrated in the central part of each lobe and are not present in the isthmus.